On the numerical assessment of flow losses and secondary flows in Pelton turbine manifolds. Issue 1 (1st September 2022) - Hahn, F J J; Semlitsch, B; Bauer, C
Abstract: Different methods combining analytical guidelines, numerical simulations, and the manufacturer's experience are employed to design and optimise the distributor manifold of a Pelton turbine. All these methods have in common to assume undisturbed straight inflow to the manifold, thus neglecting the upstream flow conditions. Our numerical simulations executed with the open-source code OpenFOAM v2012 show that the insufficient consideration of the upstream flow situation may lead to inaccurate predictions of the manifold flow. Five turbulence models were tested in our simulations, and the inflow turbulence intensity was varied from 1% to 10%. The flow quality was assessed by evaluating the head loss coefficient from total pressure drop, the head loss coefficient from the entropy production, the secondary velocity ratio upstream the injectors and the mass flow imbalances in the injectors. The study of turbulence models revealed that the k- ω Shear Stress Transport model predicted the head loss and secondary flows with reasonable accuracy. Also, the computationally less expensive model of Spalart-Allmaras leads to similar results and therefore emerges as an appropriate model for optimisation. The simulations with varying inflow turbulence intensity levels indicate a flow pattern change, if the specified inflow turbulence intensity is less than 4%. Below this value of inflow turbulence intensity, a significant increase of the secondary flow upstream of the injectors was observed.